Investigation of the Relationship between Mindful Eating Behavior and Anthropometric Measurements of Individuals Applying to a Nutrition And Diet Policlinic - Demir, Hülya; Bozyel, Elif (Jour Med Resh and Health Sci, 2022)
The calorie restriction used in obesity treatment cannot be sustainable in long-term treatments. For these reasons, different interventions are needed in addition to calorie restrictive applications. This research, which was planned and applied in a descriptive and cross-sectional pattern, was conducted in individuals over the age of 18 who applied to the Nutrition and Diet Policlinic of a private hospital. In the research, Mindful Eating Questionnaire was applied to measure individuals' socio-demographic characteristics and anthropometric information and mindful eating. NCSS (Number Cruncher Statistical System) 2007 program was used for statistical analysis.The research was carried out on 200 individuals, 81.5% of whom were women and 18.5% were men. The ages of the cases ranged between 18 and 68, with an average of 30.52 ± 10.01 years. Mindful Eating Questionnaire total scores are 3.19 ± 0.52 on average; 66.0% of cases have a score of 3 or above. Thus, healthy weight loss is achieved by reducing total calorie content. Future studies should be done to provide a standardization in the teaching of mindful eating and to demonstrate the long-term effect between disease and mindful eating. A negative correlation was found between BMI measurements and total scores in women (p <0.05). While there was a statistically significant relationship between waist circumference and hip circumference measurements and total scores in women (p <0.05), This difference was not statistically significant in men (p> 0.05). In addition to calorie restriction, it can be seen that improving mindful eating behavior may decrease body weight in obesity treatment. Therefore, it is recommended to include mindful eating application in diet treatments.